2023
DOI: 10.1021/jacs.3c09153
|View full text |Cite
|
Sign up to set email alerts
|

From Squaric Acid Amides (SQAs) to Quinoxaline-Based SQAs─Evolution of a Redox-Active Cathode Material for Organic Polymer Batteries

Marcel E. Baumert,
Victoria Le,
Po-Hua Su
et al.

Abstract: The search for new redox-active organic materials (ROMs) is essential for the development of sustainable energy-storage solutions. In this study, we present a new class of cyclobuta­[b]­quinoxaline-1,2-diones or squaric acid quinoxalines (SQXs) as highly promising candidates for ROMs featuring exceptional stability and high redox potentials. While simple 1,2- and 1,3-squaric acid amides (SQAs), initially reported by Hünig and coworkers decades ago, turned out to exhibit low stability in their radical cation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…To test this theory, we synthesized SQA-3 (Figure , R = n- butyl) using a similar strategy as for the SQX molecules involving condensation followed by N-alkylation. Consistent with the work of Hünig and Hansmann, , this class of squaramide showed a reversible redox couple in cyclic voltammetry experiments with an improved oxidation potential of 0.67 V vs Fc/Fc + (Figure a). To test the long-term stability of the resulting radical cation, we subjected this molecule to an oxidative H-cell cycling experiment (cycling between SQA-3 and SQA-3 • + ) as previously described with the earlier class of SQX squaramides.…”
Section: Results and Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…To test this theory, we synthesized SQA-3 (Figure , R = n- butyl) using a similar strategy as for the SQX molecules involving condensation followed by N-alkylation. Consistent with the work of Hünig and Hansmann, , this class of squaramide showed a reversible redox couple in cyclic voltammetry experiments with an improved oxidation potential of 0.67 V vs Fc/Fc + (Figure a). To test the long-term stability of the resulting radical cation, we subjected this molecule to an oxidative H-cell cycling experiment (cycling between SQA-3 and SQA-3 • + ) as previously described with the earlier class of SQX squaramides.…”
Section: Results and Discussionsupporting
confidence: 87%
“…This result, showing high levels of stability for what was assumed to be the radical cation of squaramide SQA-3 , is seemingly at odds with the recent finding of Hansmann and coworkers, who found that the radical cation of a very similar squaramide (from Figure , R = Me) showed rapid decomposition in EPR studies with a half-life of around 300 min and which prompted those authors to end their exploration of this class of squaramides …”
Section: Results and Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Moreover, there is plenty of room in the chemical space to tailor organic electrodes to the specific requirements of the desired electrochemical system. [145,[160][161][162][163][164][165]…”
Section: Cell Tests With Positive Electrodesmentioning
confidence: 99%
“…Even though the use of organic solvents offers an increased potential window, discovery of suitable electrolytes that allow access to extreme redox potentials (< −2 V for reduction and >+1 V for oxidation, , vs Fc/Fc + ) has been challenging due to the general scaling relationship of stability to energy density (i.e., the more extreme the potential, the more reactive the charged species). Therefore, developing electrolytes that balance stability and energy density to optimize the cell voltage remains a significant aim of the community.…”
Section: Introductionmentioning
confidence: 99%